Editorial: Reproductive barriers and gene introgression in rice species - Tao, Dayun; McNally, Kenneth L.; Koide, Yohei; Matsubara, Kazuki (Frontiers Media, 2021)
Rice (Oryza sativa L.) is one of the most widely consumed cereals both in developing and developed countries with the third-highest worldwide production (FAOSTAT, http://www.fao.org/faostat/en/#data). Rice production is constantly subject to multiple environmental stresses, both biotic and abiotic. In addition, the effect of such stresses changes in response to environmental conditions. The increasing global food demand, together with rapid population growth forces rice geneticists and breeders to speed up and push forward the improvement of resistance and/or avoidance to such stresses as well as productivity (International Rice Research Institute, https://www.irri.org/world-food-day-2020).